Exploring the Drivers of Home Births: Perspectives, Risks, Benefits, and Policy Implications in Zamboanga Sibugay, Philippines - Modillas, Marichu B.; Oliva, Dave L.; Opada, Lynne Leah M.; Gallego, Randy Ian (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: The persistence of home births in the Philippines remains conspicuous, despite the enforcement of policies discouraging this practice and the prevailing concerns about its safety. This research aims to delve into the various perspectives of women concerning home births to describe the underlying motivations behind their choices, their perceptions of the associated risks and benefits, and their stance on the “no home-birthing policy” of the state. Subjects and Method: This was a descriptive, cross-sectional study involving 80 mothers drawn from Malangas, Zamboanga Sibugay, Philippines through a referral-based sampling method. The study examined sociodemographic characteristics as independent variables, while dependent variables included perceived reasons for home birth preference, associated risks and benefits, and respondents' views on the